Improving Physicochemical Properties of Minced Fish by Adding Quail Bone Gelatin - Shahira Samsudin, Nurul; Aminal’lah, Nuraliah; Syazni Kamarudin, Ahmad; Huda, Nurul; ., . (International Journal of Engineering and Technology, 2018)
The objective of this study was to compare the physicochemical  properties (cooking yield, folding test, gel strength, expressible moisture, texture profile analysis, and color) of minced fish containing quail bone gelatin (QBG), commercial bovine gelatin (CBG), or commercial fish gelatin (CFG). QBG was prepared using two acid pretreaments: hydrochloric acid (QBGHCl) and citric acid (QBGc.a). The cooking yield of minced fish gels improved from 94.23% to 96.17–98.48% by the addition of gelatin. Addition of QBGHCl, QBGc.a, CBG, and CFG improved the folding test result from 1.00 to 2.00, reduced expressible moisture from 37.90% to 29.59, 30.19, 27.81, and 36.73%, respectively, and improved gel strength from 69.42 g.cm to 92.17, 96.5, 155.30, and 99.73 g.cm, respectively. Addition of gelatin also increased the hardness and decreased the whiteness of fish minced gels. Thus, the addition of QBG has potential as an alternative gelatin source for improving the physicochemical properties of minced fish.